PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE STAD TERHADAP HASIL BELAJAR SISWA PADA MATERI LISTRIK DINAMIS SEMESTER II KELAS X SMA NEGERI 1 RANTAU SELATAN T.P 2013/2014 - Siti Zaitun Hasibuan; Abd. Hakim Siregar (INPAFI (Inovasi Pembelajaran Fisika), 2015)
This study aims to determine the significant effect of the result cooperative learning model  to the student’s learning result in the main subject second semester X “Dynamic Power” Class in SMA Negeri 1 Rantau Selatan T.P 2013/2014.  This research is quasi experimental. The  population in this research was all students in class X which consists of 10 classes. With random cluster sampling technique was chosen class X-2 and X-1 as an experimental class and control class. Instrument were contain of multiple-choice tests and observation sheet test have been conducted to measure the student’s learning outcames. Research’s design is Control Group Pretest-Postest Design. Average data of pre-test experimental class and control class was 47.5 and 51.56. In both classes of the test data obtained pretest that both classes of data are normally distributed and homogeneous. T-test result of pretest obtained t <t table -0,04 <1.99, then Ho is accepted means the ability of the students at the beginning of the second class of the same. Then given treatment that is experimental class with cooperative learning model STAD and a control class with conventional learning models. The posttest average yield experimental class and control class is 70.5 dan 61.5. In both classes of the test data obtained posttest that both classes of data are normally distributed and homogeneous. T test results obtained t> t table 3.09> 1.99 then the Ha was accepted that no significant influence cooperative learning model STAD to the student learning outcomes. Keywords   : Cooperative type STAD, activity, learning results